2013
DOI: 10.1126/scisignal.2003295
|View full text |Cite
|
Sign up to set email alerts
|

BSTA Promotes mTORC2-Mediated Phosphorylation of Akt1 to Suppress Expression of FoxC2 and Stimulate Adipocyte Differentiation

Abstract: Phosphorylation and activation of Akt1 is a crucial signaling event that promotes adipogenesis. However, neither the complex multistep process that leads to activation of Akt1 through phosphorylation at Thr308 and Ser473 nor the mechanism by which Akt1 stimulates adipogenesis is fully understood. We found that the BSD domain–containing signal transducer and Akt interactor (BSTA) promoted phosphorylation of Akt1 at Ser473 in various human and murine cells, and we uncovered a function for the BSD domain in BSTA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 61 publications
0
38
1
Order By: Relevance
“…However, FoxO1/3 phosphorylation is not affected in Rictor-deficient BAT; thus, if the metabolic shift is driven by FoxO1/3, it may be through an alterative mechanism such as acetylation (Banks et al, 2011; Masui et al, 2013). Another possibility is that FoxC2 mediates the metabolic shift (Cederberg et al, 2001; Yao et al, 2013); however, we do not observe any change in FoxC2 expression in Rictor-deficient preadipocytes (not shown), nor do we see effects on the FoxC2 targets C/ebpβ or Wnt10b during differentiation (Gerin et al, 2009). The shift could also bemediated through unidentified AKT substrates thatuniquelyrequirehydrophobic motif phosphorylation.…”
Section: Discussionmentioning
confidence: 58%
“…However, FoxO1/3 phosphorylation is not affected in Rictor-deficient BAT; thus, if the metabolic shift is driven by FoxO1/3, it may be through an alterative mechanism such as acetylation (Banks et al, 2011; Masui et al, 2013). Another possibility is that FoxC2 mediates the metabolic shift (Cederberg et al, 2001; Yao et al, 2013); however, we do not observe any change in FoxC2 expression in Rictor-deficient preadipocytes (not shown), nor do we see effects on the FoxC2 targets C/ebpβ or Wnt10b during differentiation (Gerin et al, 2009). The shift could also bemediated through unidentified AKT substrates thatuniquelyrequirehydrophobic motif phosphorylation.…”
Section: Discussionmentioning
confidence: 58%
“…Consistently, loss of Rictor in adipose precursors cells or MEFs impairs adipogenesis in vitro (42, 138). Mechanistically, it was proposed that mTORC2 affects early adipogenesis by blocking the activity of the transcription factor forkhead-box C2 (FoxC2), downstream of Akt (138) (Figure 4b). The combination of results from all these studies suggests that mTORC2 is required for early adipogenesis but likely dispensable for the terminal differentiation and the maintenance of mature adipocytes.…”
Section: Mtorc2mentioning
confidence: 99%
“…However, in these studies the rictor gene was knocked out only in mature adipocytes or during the terminal phase of adipocyte differentiation, which may not be able to reveal the exact role of mTORC2 in early adipocyte differentiation. In fact, several recent studies demonstrated that mTORC2-mediated phosphorylation of Akt1 promoted adipogenesis by suppressing the expression of FoxC2, and Rictor-null mouse embryonic fibroblasts (MEFs) are incapable of differentiating into adipocytes [55-57]. In addition, Rictor-deficient brown adipocyte precursor cells are unable to differentiate and synthesize lipid droplets in vitro [58].…”
Section: Role Of Mtor Signaling In Adipogenesismentioning
confidence: 99%